Analyzing the Causes, Consequences and Solutions of Investment in Post Reform Surabaya - Nuralifia, Dyah Febiyani; Yasin, Muhammad (Journal International Dakwah and Communication, 2023)
Increased investment can help drive a country's economic development. In macroeconomics, investment also functions as a component of national income, gross domestic product, or gross domestic product. Investment is positively correlated with GDP or national income, when investment increases, GDP increases, and when investment decreases, GDP decreases. In the same context, Harrod-Domar developed a very legendary theory that economic growth requires capital formation in addition to capital stock. Capital formation can be seen as spending that increases the economy's ability to produce goods, or as spending that increases the effective demand for society as a whole. This requires investment to increase the ability to produce goods and services needed in the economy. Therefore, high and sustainable levels of economic growth are generally supported by increased exports and investment. In addition, Harrod-Domar emphasized that every economy must allocate a certain percentage of national income to replace damaged capital goods as an effort to grow the economy, thus requiring new investment as a capital stock.